2018
DOI: 10.3892/mmr.2018.9687
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin‑loaded dual‑functional hyaluronic acid nanoparticles: Preparation, characterization and antitumor efficacy in�vitro and in�vivo

Abstract: A novel GHH copolymer was synthesized using hyaluronic acid modified with glycyrrhetinic acid and L-histidine (His), and doxorubicin-loaded GHH nanoparticles (DOX/GHH) were prepared for liver-targeted drug delivery and pH-responsive drug release. In the present study, GHH nanoparticles were characterized, and their pH-responsive behaviors were evaluated at different pH levels. The antitumor effect of the DOX/GHH nanoparticles was investigated in vitro and in vivo. Results showed that the DOX/GHH nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…As a result of these considerations, morphological and structural features of the NPs are the outcome of the modulation of different factors involved in the microfluidic ionotropic gelation process, as shown in Figure 5 , which demonstrates how the chosen process parameters enable an ease shift in the architecture changing from coprecipitates to different core–shell structures. Such a design strategy, pushed to the molecular level, not only leads to a fine control over the nanoarchitecture but, above all, it is also crucial in determining the functional properties of the nanocarrier, making it relevant not only in the field of precision medicine but also in other areas of medicine and biology [ 88 , 89 , 90 , 91 , 92 ]. Indeed, a considerable advantage of the proposed approach consists of the opportunity to obtain a relaxivity boost of the encapsulated CAs for MRI ( Figure 7 ) by changing the structural parameter of the hydrogel matrix and exploiting the Hydrodenticity concept, as underlined by Russo et al [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these considerations, morphological and structural features of the NPs are the outcome of the modulation of different factors involved in the microfluidic ionotropic gelation process, as shown in Figure 5 , which demonstrates how the chosen process parameters enable an ease shift in the architecture changing from coprecipitates to different core–shell structures. Such a design strategy, pushed to the molecular level, not only leads to a fine control over the nanoarchitecture but, above all, it is also crucial in determining the functional properties of the nanocarrier, making it relevant not only in the field of precision medicine but also in other areas of medicine and biology [ 88 , 89 , 90 , 91 , 92 ]. Indeed, a considerable advantage of the proposed approach consists of the opportunity to obtain a relaxivity boost of the encapsulated CAs for MRI ( Figure 7 ) by changing the structural parameter of the hydrogel matrix and exploiting the Hydrodenticity concept, as underlined by Russo et al [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of the formulation was evaluated in human hepatoma cell line HepG2 and H22 tumor-bearing mice. The targeted formulations were found to be more effective against tumors than the free drug [52]. Han et al…”
Section: Hyaluronic Acid-based Nanoparticles For Cancer Therapymentioning
confidence: 99%
“…The cytotoxicity of the formulation was evaluated in human hepatoma cell line HepG2 and H22 tumor-bearing mice. The targeted formulations were found to be more effective against tumors than the free drug [ 52 ]. Han et al prepared a formulation for controlled release and targeted delivery of doxorubicin to the nuclei of squamous cell carcinoma cells (SCC7 cells).…”
Section: Drug Delivery Systems For Cancer Treatmentmentioning
confidence: 99%
“…Therefore, HA is an ideal carrier polymer in the construction of NPs for the targeted delivery of drugs. Numerous studies have indicated that GA-functionalized hyaluronic acid NPs selectively target liver tumor tissue and liver cancer cells and reduce adverse reactions when loaded with antitumor drugs, such as doxorubicin (DOX), paclitaxel (PTX) and 5-fluorouracil (20)(21)(22). Docetaxel (DTX), a member of the taxane family, is a semi-synthetic analogue of PTX and a microtubule depolymerization inhibitor (23).…”
Section: Introductionmentioning
confidence: 99%